PRINSIP NEED FOR COGNITION UNTUK DESAIN IKLAN - Mangestuti, Retno (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2008)
Stressing only on creative strategyÂ  (theme, lay out, color, typography, or special effect), it has not been sufficient yet, for designing an advertisement. We need to consider need for cognition (NFC) of consumers. NFC is individual need for think and understand information carefully and clearly.Understanding NFC of consumers properly will make the design of an advertisement appropriate its aim, means that an advertisement get to the point of delivering information of product and influence the attitude of consumers to the product.Keywords: advertisement, need for cognition (NFC), and consumers.